Exploring the Therapeutic Potential of Antiaris africana: Targeting Cyclin-Dependent Kinases 8 and 13 for Cancer Treatment through Molecular Docking Studies - Alabi, Mutiu A.; Oladoye, Elizabeth O.; Adedokun, Taofeeq A.; Adebiyi, Adelowo A.; Olatoye , Raphael S.; Ajani , Beloved K.; Ibrahim, Damasuno S.; Olayiwola, Halimah; Enobiomanor, Racheal I.; Ajani, Emmanuel O. (Al-Mustansiriyah Journal of Science, 2025)
Background: Cancer remains a major global health burden that significantly affects human populations. The ongoing need for innovative therapeutic strategies to both manage and prevent this life-threatening disease is paramount. The quest for creative and less toxic cancer therapies has led to a vast exploration of plant-derived compounds. Objective: This study investigated the anticancer potential of phytochemicals extracted from Antiaris africana (A. africana), a traditional medicinal plant used in ethnomedicine in West Africa, through molecular docking studies. Methods: The stem bark extract, prepared via maceration with methanol, was analyzed by gas chromatography mass spectrometry (GC-MS), revealing 36 bioactive compounds. In silico evaluations, including molecular docking, ADME prediction, and toxicity assessments, were carried out to identify inhibitory effects on cyclin-dependent kinases 8 (CDK8) and 13 (CDK13), key regulators of cancer progression. Results: GC-MS analysis of the methanolic extract of A. africana revealed 36 phytochemicals with possible anticancer potential. Notable phytochemicals, such as bis(2-ethylhexyl) phthalate and campesterol, exhibited significant binding affinities to CDK8 and CDK13, with high Glide scores and favorable pharmacokinetic profiles, adhering to Lipinski’s five rule. ADME analyzes highlighted the druglikness and minimal toxicity of the compound, supporting its potential as an orally bioavailable therapeutic. In silico studies revealed bis(2-ethylhexyl) phthalate, 2,6,10,15,19,23-hexamethyl-tetracosa-2,10,14,18,22-pentaene-6,7-diol and 3-12-formyl-digoxigenin as lead compounds, which offered promising insights into the anticancer potential of the compounds. Conclusions: This study underscores A. africana as a promising source of lead compounds for targeted cancer therapies. Further in vitro and in vivo studies are recommended to validate these findings and explore the therapeutic landscape of these bioactive molecules.